Restoring the primacy of technological innovation. (1st March 2015) - Kingston, William
Abstract : The industrial revolution depended upon a system of individual property rights which was unusually capable of forcing self-interest to serve the public good as well. This system led to unprecedented growth of wealth, primarily because it encouraged technological innovation. Over time, however, the laws of property (notably those relating to the corporation and to information protection) were captured by those who could benefit from them. In particular, financiers were released from the disciplines which had applied to them since the invention of money, and this made investment in financial innovation more attractive than technology. During the first part of the industrial revolution, growth in credit meant growth in wealth, but there is now a mass of empirical evidence that this correlation has turned negative. A series of proposals for reversing this trend is offered, specifically changes in corporation law and new means for protection of information. These include measuring grants of privilege by money instead of time, compulsory expert arbitration of disputes, and protection of innovation directly instead of indirectly, which is all that patents purport to offer. It is also argued that public provision of finance for innovation should generally follow a US model (which is described) rather than the practice of the EU, and that funding of university research should be transmitted through firms to a much greater extent than at present. A variant of an earlier Central Policy Review Staff experiment in the UK is suggested as offering some chance of introducing these reforms in the face of politicians' vulnerability to interest pressures.